2011
DOI: 10.4061/2011/741213
|View full text |Cite
|
Sign up to set email alerts
|

Superior Therapeutic Potential of Young Bone Marrow Mesenchymal Stem Cells by Direct Intramyocardial Delivery in Aged Recipients with Acute Myocardial Infarction: In Vitro and In Vivo Investigation

Abstract: Introduction. Bone-marrow-derived mesenchymal stem cells (MSCs) have been studied for treatment of myocardial infarction (MI). Since MSCs from older donors show quantitative and qualitative senescent changes, we hypothesized that a better outcome may be achieved if aged recipients are given MSCs obtained from young donors, rather than using their own autologous MSCs. Methods. In vitro studies compared properties of young and old MSCs. Aged rats randomized into 3 groups underwent coronary artery ligations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…They are easy to isolate from bone marrow, adapt to ex vivo expansion and differentiate into various cell lineages in vitro and in vivo without any ethical concerns or immunological rejection (15). In vivo and in vitro studies showed that the source of stem cells is crucial for successful implantation (16). MSCs harvested from young rodents demonstrated significantly increased cellular proliferation, greater resistance to hypoxic conditions and improved differentiation compared with MSCs obtained from older rodents.…”
Section: Discussionmentioning
confidence: 99%
“…They are easy to isolate from bone marrow, adapt to ex vivo expansion and differentiate into various cell lineages in vitro and in vivo without any ethical concerns or immunological rejection (15). In vivo and in vitro studies showed that the source of stem cells is crucial for successful implantation (16). MSCs harvested from young rodents demonstrated significantly increased cellular proliferation, greater resistance to hypoxic conditions and improved differentiation compared with MSCs obtained from older rodents.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in their study, MSCs were harvested from the sternum of patients undergoing cardiac surgery. These cells, taken from elderly donors, were previously shown to have a significantly lower capacity for differentiation, angiogenesis, survival, and even proliferation [6, 7, 41]. It is of interest to note that, in the in vitro studies, human MSCs used were instead harvested from young healthy donors.…”
Section: Evidence From In Vivo Studiesmentioning
confidence: 99%
“…Furthermore, most of the patients who could benefit from such therapy are elderly patients with multiple medical comorbidities. Unfortunately a number of recent studies have documented that mesenchymal stem cells (MSCs) obtained from elderly donors, and those with diabetes, renal failure, or severe ischemic heart disease, demonstrate significantly reduced capacity for proliferation, differentiation, and neovascularization, with increased levels of apoptosis in vitro and in vivo [6, 7]. Such impaired autologous donor cells from sick elderly patients could therefore limit their therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%
“…A major problem in the use of MSCs is the transplantation environment [13]. For example, 90% of MSCs were shown to be apoptotic, which resulted in programmed cell death, within 3 days after transplantation into the heart for cardiomyocyte infarct repair [1415]. In the last few years, the effects of inflammation induced immunosuppression has been taken into account in the use of rational design for the clinical use of MSCs.…”
Section: Introductionmentioning
confidence: 99%